1969
DOI: 10.1139/v69-224
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on the rates of hydrolysis of allyl chlorides

Abstract: The pressure dependence of the rates of hydrolysis of allyl chloride and a-, P-, and I-methyl ally] chlorides has been examined. The significance of the activation volumes, AV*, and their pressure dependence, dAV4/dP, is discussed. These activation parameters indicate an SN2 mechanism for allyl and 13-methyl allyl chloride and an SN1 or intermediate character mechanism for the other methyl substituted allyl chlorides investigated. The results are compared with the corresponding AHY and ACp* measurements of Rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1971
1971
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…There are some limited experimental data with which to compare the present calculations. The bulk of the experimental data available for allyl chloride has been interpreted to suggest that it reacts primarily via the S N 2 mechanism in most organic solvents. ,,, This is consistent with our calculations; a very large dielectric constant, like that for water, is required to bring the free energy of activation for the S N 1 process below that for the S N 2. We note that Brubacher et al studied the hydrolysis of allyl chloride in water in 1968, and reported a 298 K Δ G ⧧ of 25.5 ± 2 kcal mol -1 for this process.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…There are some limited experimental data with which to compare the present calculations. The bulk of the experimental data available for allyl chloride has been interpreted to suggest that it reacts primarily via the S N 2 mechanism in most organic solvents. ,,, This is consistent with our calculations; a very large dielectric constant, like that for water, is required to bring the free energy of activation for the S N 1 process below that for the S N 2. We note that Brubacher et al studied the hydrolysis of allyl chloride in water in 1968, and reported a 298 K Δ G ⧧ of 25.5 ± 2 kcal mol -1 for this process.…”
Section: Resultssupporting
confidence: 87%
“…In the majority of nonaqueous solvents, experimental studies have been interpreted to indicate that crotyl chloride also seems to prefer the S N 2 pathway, ,, consistent with the CCl 4 predictions in Table (as an example of a nonpolar medium) and Figure . In aqueous solvents, however, it has been variously reported that crotyl chloride hydrolyses can be S N 2, , S N 1, , or a mixture of both. , The predictions in Table suggest, however, that the S N 1 pathway should strongly dominate over the S N 2 for crotyl chloride in water. Brubacher et al .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The hydrolysis of benzyl chloride (8), isopropyl bromide (I), and ally1 chloride (2) have been studied by previous workers and their ratelpressure data were used in the determinations of dVt/dTfor these compounds.…”
Section: Benzylmentioning
confidence: 99%